Why Are There More Accidents on Mondays? Economic Incentives, Ergonomics or Externalities - Michelle Poland; Isabelle Sin; Steven Stillman (Institute of Labor Economics (IZA), 2019)
Research consistently finds more workplace injuries occur on Mondays than on other weekdays. One hypothesis is that workers fraudulently claim that off-the-job weekend sprains and strains occurred at work on the Monday in order to receive workers' compensation. We test this using data from New Zealand, where compensation is virtually identical whether or not an injury occurs at work. We still find that work claims, especially sprains and strains, occur disproportionately on Mondays, although less than in other jurisdictions. This suggests fraudulent claims in other countries are just one part of the story. Furthermore, we find work claims remain high on Tuesdays, and that workers' sprains and strains that occur off-the-job also disproportionately fall on Mondays. Sprains and strains treated at hospitals, which are not closed over the weekend, are also elevated on Mondays. However, Monday lost-time injuries are less severe than injuries on other days. Our findings are consistent with a physiological mechanism contributing to elevated Monday injury claims in New Zealand, but do not suggest doctors' offices being closed over the weekend, ergonomic explanations, or work being riskier on Mondays play important roles.
Keywords: I18; I13; J38; 330; monday effect; workers compensation; accidents; incentives